Effect of Customer Relationship Management on Organisational Resilience of Deposit Money Banks in Nigeria - Edeh, Friday Ogbu; Ugboego, Chukwu Agnes; Chibuike, Osueke Nelson (International Journal of Economics, Business and Management Studies, 2019)
This study investigates the effect of customer relationship management on organisational resilience of deposit money banks in Nigeria using cross-sectional research survey. Simple random sampling was used to select ten deposit money banks in Abakaliki, Ebonyi State. Eighty senior managers were sampled from ten deposit money banks in Abakaliki. Sample size of sixty six was ascertained from the accessible population with Krejcie and Morgan. Closed ended questionnaire was used to collect data from the respondents’. Face validity approach was employed to ascertain the validity of the instrument. Cronbach α was used to determined the reliability of instrument. Frequency distribution was used to analyse participants’ demographic characteristics while simple linear regression was used to analyse the hypotheses with IBM SPSS Statistics (20.0). The study found that customer relationship management has positive significant effect on organisaional resilience of deposit money banks in Nigeria. The study concludes that customer relationship management measured in terms of people, process and technology dimensions promotes organisational resilience measured on openness, proaction and authenticity in the service oriented organizations. It was recommended that managers of deposit money banks in Nigeria and sub-Saharan Africa should embrace customer relationship management that is geared towards employee collaboration, quality service delivery, customer satisfaction and customer information management.